Analytical characterization of broadly neutralizing antibody CAP256LS heavy chain clipping during manufacturing development. (29th August 2022) - Gollapudi, Deepika; Rosales‐Zavala, Erwin; Ivleva, Vera B.; Yang, Yanhong; Li, Yile; O'Connell, Sarah; Doria‐Rose, Nicole A.; Patel, Aakash; Blackstock, Daniel; Gowetski, Daniel B.; Carlton, Kevin; Gall, Jason G. D.; et al.
Abstract: Broadly neutralizing antibody (bNAb) CAP256‐VRC26.25 (abbreviated CAP256LS), a human IgGI monoclonal antibody targeting the V1V2 site of the HIV‐1 envelope, has demonstrated high therapeutic potential as a broadly neutralizing monoclonal antibody against HIV‐1. During the process development, a heavy chain fragmentation (clipping) was observed, that led to a relative potency reduction. In this report, we highlighted a series of process and product mitigation strategies deployed to advance this product. We have detailed how analytical characterization tools, especially the microchip reduced capillary gel electrophoresis (CGE‐SDS), played a pivotal role in identifying the development issues and in providing measurements to guide implementation of mitigation strategies.